102 AN UNUSUAL PRESENTATION AND TREATMENT FOR PHEOCHROMOCYTOMA. (1st January 2006) - Bahar, A.; Purnell, J. Q.; Schuff, K. G.
Abstract : Background: Pheochromocytoma is a rare condition and is difficult to diagnose as it overlaps more common disorders. Delay in treatment can be fatal and tumor size can affect its presentation/management. Objective: Present an unusual case of pheochromocytoma and discuss embolization as a therapy. Case Presentation: A 41 yo woman presented with chest pain, diaphoresis, hypertension, and tachycardia. Right arm blood pressure (BP) was 248/137, left arm BP was 161/121, and pulse was 131. She had several months of "spells" of posterior headaches, chest/abdominal pain, palpitations, and elevated BP. Contrast CT excluded aortic dissection but revealed a 9.1 × 9.4 × 8.6 cm hypervascular, well encapsulated right adrenal mass with areas of necrosis. A presumptive diagnosis of pheochromocytoma was made. Within 12 hours of admission to the ICU, her hematocrit dropped and she became hypotensive. Massive fluid and blood transfusion was followed by systemic hypertension and a rise in intra-abdominal pressure consistent with abdominal compartment syndrome. Emergency laparotomy revealed a large right retroperitoneal hemorrhage. Because of hemodynamic instability and continued hemorrhage, coil embolization of the mass was performed, eliminating 95% of the tumor's blood supply. IV phentolamine was required during the embolization and for 4 additional days, after which BP was easily controlled on oral prazosin. Several weeks later, the remnant mass was removed. Histology revealed no cytologic features of malignancy and no invasion of the surrounding structures with 20 to 30% of the tumor still viable. Discussion: Pheochromocytoma is an uncommon etiology for common symptoms, occasionally diagnosed during a hypertensive crisis. Because of alpha receptor stimulation and intravascular volume depletion, beta blockers cannot be used alone. Phentolamine could not be easily obtained and nitroprusside's metabolism to cyanide limited its use in multi-organ failure. Large tumors pose unique issues. Massive retroperitoneal hemorrhage can occur after spontaneous rupture and control of hemorrhage can be surgically challenging. Coil embolization allowed rapid hemostasis but hemodynamic instability can occur after embolization, likely due to release of stored catecholamines from the infarcting tissue. Furthermore, even with successful embolization, viable remnant tissue may persist, requiring adequate preop preparation if eventual surgical excision is planned. Large tumors also raise the concern of malignancy. Even with seemingly complete surgical resection, 14% of tumors recur and 10% have metastases; hence, continued medical reevaluation for biochemical/anatomic evidence of tumor recurrence is recommended.